World productivity growth: a model averaging approach - Duygun, Meryem; Hao, Jiaqi; Isaksson, Anders; Sickles, Robin C. (Wiley, 2017)
Policy makers and the economic researchers who provide them estimates of economic activity need to have an informative and scientifically-based method to develop a consensus estimate for the most basic of the productivity measures, total factor productivity (TFP) growth. We discuss methods to combine the various estimates based on different empirical specifications that model and estimate productivity growth. We also discuss the various econometric approaches used in the profession to estimate productivity growth. Our focus is on world TFP growth.